2014
DOI: 10.1016/j.cryobiol.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Dendroides canadensis antifreeze proteins as potential ingredients in cryopreservation solutions

Abstract: Expanding cryopreservation methods to include a wider range of cell types, such as those sensitive to freezing, is needed for maintaining the viability of cell-based regenerative medicine products. Conventional cryopreservation protocols, which include use of cryoprotectants such as dimethylsulfoxide (Me2SO), have not prevented ice-induced damage to cell and tissue matrices during freezing. A family of antifreeze proteins (AFPs) produced in the larvae of the beetle, Dendroides canadensis allow this insect to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…The difference in viability at concentrations ≥0.1 mg/ml was subtle. Interestingly, at 1 mg/ml LeIBP, the viability decreased slightly, which is similar to that observed with the MECs of red blood cells (RBCs), ram spermatozoa, rat smooth muscle cells, and immature rat oocytes when exposed to AFPs/IBPs [11,15,27,32]. In those experiments, the use of high amounts of AFPs/IBPs was related to a decrease in the viability of cryopreserved biological samples.…”
Section: Minimum Effective Concentration Of Leibp For Cryopreservationsupporting
confidence: 77%
See 1 more Smart Citation
“…The difference in viability at concentrations ≥0.1 mg/ml was subtle. Interestingly, at 1 mg/ml LeIBP, the viability decreased slightly, which is similar to that observed with the MECs of red blood cells (RBCs), ram spermatozoa, rat smooth muscle cells, and immature rat oocytes when exposed to AFPs/IBPs [11,15,27,32]. In those experiments, the use of high amounts of AFPs/IBPs was related to a decrease in the viability of cryopreserved biological samples.…”
Section: Minimum Effective Concentration Of Leibp For Cryopreservationsupporting
confidence: 77%
“…Taken together, the MEC for the cryopreservation of mammalian cells is 0.1 mg/ml LeIBP. However, owing to the variation between cell types and the effect of the composition of the cryopreservation solution on IBPs, the MEC should be verified empirically before adopting this strategy for cryopreservation [1,2,11,15,21,22,24,27,39,44]. For example, for the vitrification of mouse ovarian tissues, the MEC of LeIBP was 10 mg/ml in DPBS containing 20% FBS, 7.5% ethylene glycol, 7.5% DMSO, and 0.5 M sucrose [24], whereas for the cryopreservation of RBC, 0.8 mg/ml LeIBP was optimal in 40% glycerol [27].…”
Section: Minimum Effective Concentration Of Leibp For Cryopreservationmentioning
confidence: 99%
“…The implications of this finding are significant because it opens up the possibility of producing short, robust, non-cysteine analogues of the hyperactive disulfide rich AFPs for use as cryoprotectants in various fields. 18,32 We further demonstrate that, even though disulfide bridging is not crucial, an intra-coil bridging of some sort is absolutely essential for antifreeze activity in the DCR family. Linear versions of the 26 and 39-mer peptides were synthesized by substituting the cysteines with alanines as well as a version of the 39-mer peptide with the cysteines in the reduced and alkylated forms.…”
mentioning
confidence: 95%
“…[15][16][17] Recombinantly expressed DcAFP proteins have been studied to assess their icestructuring patterns and potential for use in mammalian cell cryopreservation. 18 However, their large size and complex nature (e.g. presence of multiple disulfides), make their commercial potential harder to achieve.…”
mentioning
confidence: 99%
“…Whether or not AFPs are protective or damaging depends mainly on formulation characteristics involving the concentrations and types of AFPs and cryoprotectants [289]. For example, Halwani et al [118] have shown that AFPs from the beetle Dendroides Canadensis can be beneficial in preservation compositions containing Me2SO. AFPs have also been shown to interact with cell membranes in a way that is protective for chill-sensitive cell types [253,254].…”
Section: Nature Evolution and Avoiding Ice Formation Injury: Antifrmentioning
confidence: 99%